Spasticity and Intrathecal Baclofen - Furr-Stimming, Erin; Boyle, Allison M.; Schiess, Mya C. (Seminars in Neurology, 2014)
Severe spastic tone and/or spastic hypertonia can be the most disabling consequences of a neurologic insult, resulting from an excess of muscle tone. Baclofen, a GABA-B agonist, is one of the most widely used drugs in treating abnormal or disabling spastic tone. However, the effectiveness of baclofen taken orally is often limited by its systemic side effects, including sedation, confusion, and lethargy. Intrathecal baclofen (ITB) delivered by an implanted catheter can work directly at the spinal cord level to reduce spastic tone through presynaptic inhibition. Several decades after Penn and Kroin (1984) proved that continuous infusion of intrathecal baclofen reduced spinal cord spasticity, numerous studies have demonstrated the benefits of ITB therapy and proven its effectiveness in modulating and reducing spastic tone. In this article the authors review current methods of management with ITB therapy; summarize the current knowledge, controversies, and available scientific literature; illustrate through different clinical cases treatment strategies and their outcomes; and lastly, provide a synopsis of current clinical practice in ITB therapy with insights into new therapeutic developments.
Keywords: intrathecal; baclofen; spastic tone; GABA; hypertonia; hyperreflexia; infusion mode